Investigation on the Factors Affecting Cronobacter sakazakii Contamination Levels in Reconstituted Powdered Infant Formula - Parra-Flores, Julio; Rodriguez, Alejandra; Riffo, Francisca; Arvizu-Medrano, Sofía M.; Arias-Rios, E. Verónica; Aguirre, Juan (Frontiers in Pediatrics, 2015)
Introduction: Certain strains of Cronobacter sakazakii can cause serious invasive infections in children, mainly those less than 2 months old and fed with powdered infant formula (PIF). The infectious dose of C. sakazakii is unknown but evidence suggests that it is approximately 1000 CFU. Powdered infant formula is currently considered safe if its end-product C. sakazakii level is <1 CFU/g. In this study, we determined the lag time, generation time, and growth rate of five pooled C. sakazakii isolates to evaluate the factors affecting contamination levels in reconstituted PIF. Methods: 1.71 log CFU/ml of C. sakazakii were inoculated into 100 ml and 3000 ml of reconstituted PIF and incubated at 22 °C and 35 °C. Growth was evaluated over a 24-h period. ComBase was used for modeling. Results: In 3000 ml, the growth rate was 0.45 ± 0.02 log CFU/h with a lag phase of 3±0.05 h and generation time of 0.67 h at 22 °C, while the growth rate was 0.73 ± 0.01 log CFU/h with a lag phase of 0.45±0.03 h and generation time of 0.41 h at 35 °C. Conclusions: C. sakazakii grows rapidly in reconstituted PIF, especially at 35 °C.